HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DENGAN KEPATUHAN MENGONSUMSI TABLET TAMBAH DARAH PADA SISWI DI SMA ADABIAH 2 KOTA PADANG - Nurhalifah Putri, Siti; Meta Rikandi (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2025)
Anemia is a common blood disorder marked by reduced red blood cells, which can cause health problems since hemoglobin in these cells carries oxygen throughout the body. This study aimed to examine the relationship between adolescent girls’ knowledge and attitudes toward iron supplementation and their adherence to consuming iron tablets (TTD) among female students at SMA Adabiah 2 Padang. Conducted on June 12, 2025, the research used an analytical observational design with a cross-sectional approach. The population consisted of adolescent girls at the school, with 78 respondents selected through stratified random sampling. Data were analyzed using univariate and bivariate methods with computerized processing. Results showed that 84.6% of students complied with iron tablet consumption, while 15.4% did not. Statistical analysis revealed no significant relationship between knowledge and compliance (p-value 0.059 > 0.05). Similarly, attitudes showed no significant correlation with compliance (p-value 0.154 > 0.05), although most students with positive attitudes were compliant. In conclusion, knowledge and attitudes were not directly related to adherence. The study emphasizes the need for students to improve their understanding of the importance of iron supplementation to prevent anemia, safeguard health, support learning, and prepare for their future roles as mothers.